Farm Household Incomes in OECD Member Countries over the Last 30 Years of Public Support - Bruno Henry de Frahan; Jérémie Dong; Rembert De Blander (Luxembourg Income Study (LIS), 2017)
At a time when policy-makers in many developed countries continue to justify farm support on the basis of relatively low and unstable incomes, this chapter shows that incomes of farm households are not particularly lower on average compared to those of non-farm households in most of the ten selected OECD member countries. What is however striking is that income disparity and poverty are greater in the farm community compared to the non-farm community in most of the selected countries. This analysis questions therefore the continuation of indiscriminate farm income support. It also calls for the need of collecting farm household data that would allow a more effective targeting of farm support and for revising fundamentally public interventions towards the agricultural sector.
Keywords: Q12; Q18; 330; farm household income; farm problem; LIS data; OECD countries